QS10: Morphological Changes Of Skin Related To Acellular Dermal Matrix Incorporation In Tissue Expansion - Applebaum, Sarah A. (Plast Reconstr Surg Glob Open, 2021)
PURPOSE: Acellular dermal matrix (ADM) is used to create an inferolateral sling nearly three-quarters of the time in breast reconstruction and has proven a valuable alternative to total submuscular coverage of the implant. Previous work has demonstrated decreased inflammation and fibrosis of the pocket lining the ADM sling; however there has been minimal investigation into the role of ADM in skin growth and regeneration. The present study evaluates morphologic and molecular changes mediated by use of ADM in tissue expansion. METHODS: Two tissue expanders, one wrapped in ADM, were placed subcutaneously on the back of Yucatan minipigs. All expanders were inflated with two weekly fills of 60cc of normal saline and skin biopsies were harvested after two weeks of expansion from each condition: control, tissue expansion (TE), and tissue expansion with ADM (TE+ADM). Three biopsies per condition were embedded in paraffin or OCT medium and stained with Russell Movat Pentachrome and Immunofluorescence of CD31, respectively. Collagen in the papillary dermis of pentachrome-stained images were analyzed using an ImageJ plug-in, Fibril Tool, that applies circular statistics to estimate average fibril orientation as the direction angle from -90 to 90 with respect to the x-axis. One-way ANOVA evaluated seventy-two measurements per condition and post-hoc analysis with Tukey’s HSD test identified significant comparisons between the groups. Number of fluorescent cells expressing CD31 (a marker of endothelial cells) were counted on 12 photographs per condition. P-values ≤ .05 were considered significant. Total deformation was calculated using a computational model and isogeometric analysis. RESULTS: The mean fibril orientation of TE and TE+ADM underwent -85% change (P < .001) and -15% change (P = .65), respectively, compared to control. Three times more CD31(+) cells were observed in TE+ADM compared to control (P < .001), but no significant changes were detected in TE alone. Histogram of total deformation revealed more even distribution of forces in TE+ADM compared to TE and control. CONCLUSIONS: The use of ADM in a porcine tissue expansion model appears to mitigate disarray of the collagen network in adjacent tissue, thereby creating a more extensive, yet even, distribution of stretched skin. This observation, combined with the finding of increased angiogenesis, suggests it is the incorporation of ADM that confers these protective benefits. Future studies will evaluate whether the protective effects of ADM can serve to improve TE in compromised tissue beds, as seen in patients undergoing TE concurrent with perioperative radiation therapy.